THE IMPORTANCE OF THE COMMUNICATIVE ENVIRONMENT BETWEEN TEACHER AND STUDENT IN LEARNING ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article highlights the importance of creating a communicative environment between teachers and students in the process of learning English. As one of the modern approaches in language teaching, the communicative method encourages students to engage in active communication, express ideas freely, and use the language in real-life situations. The article analyzes the role of a positive communicative atmosphere in increasing students’ motivation, enhancing learning efficiency, and developing their communicative competence. Furthermore, the advantages of interactive teaching methods—such as pair and group work, role-playing, and discussion activities—are demonstrated through practical examples. The results of the study indicate that establishing a sincere and trust-based communicative environment in the classroom increases students’ engagement and improves their ability to think and communicate effectively in English.